INTERAKSI DIGITAL MELALUI VIDEO ANIMASI 2D BANGUN RUANG UNTUK SISWA SEKOLAH DASAR - Pratiwi, Merina; Kurniawan, Indra; Syarief, Amiroel Oemara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Digital interaction through 2D animation videos provides an engaging and effective learning method for elementary school students, particularly in understanding geometric shapes. This community service project aims to develop innovative learning media in the form of interactive 2D animation videos to help students visualize the characteristics of geometric shapes clearly and enjoyably. The development process involves several stages, including needs analysis, design, production, and evaluation of the media's effectiveness in enhancing students' comprehension. The results indicate that the use of interactive 2D animation videos improves learning interest, concept understanding, and student participation during the learning process. Teachers also appreciated this media as a relevant and curriculum-aligned teaching aid. It is expected that this media can serve as an inclusive and easily applicable technology-based learning solution in various elementary educational settings.